End-of-life scenarios for bioplastic food and drinking packages : a study of Swedish bioplastic waste disposal habitsand environmental impacts - Hansson, Tilda (SLU/Department of Molecular Sciences, 2018)
The aim of this study was to investigate real end-of-life scenarios for some of the most common bioplastics, such as PLA and Bio-PET, for food and drinking packages in Sweden and to evaluate some of the potential environmental consequences of these scenarios. Life Cycle Analysis often evaluate intended end-of-life scenarios for bio-plastic products, but this study used an explorative research method, gathering infor-mation of the conduction and habits of bioplastics to evaluate if these scenarios were the ones occurring. For the bioplastic to take an intended life cycle path, all the actors such as producers, consumers and municipals, must perform. Bioplastics are material which have a growing market owing to strategies for an environmentally friendly and sustainable society. This study explored the paths of bioplastics from consumer dis-card to end-of-life scenario but also evaluated some of the potential environmental consequences that can occur due to these paths, using a descriptive literature study. The results showed that PLA and Bio-PET bottles are institutionally handled very differently. Bioplastics are incinerated, recycled or thrown as environmental litter. These scenarios give a variety of environmental consequences such as various amounts of greenhouse gas-emissions due to different treatment processes and phys-ical damage to animals and ecosystems due to deficiency in biodegradation. This study explored and evaluated different paths of bioplastics in the society with the conclusion that there is a lack of institutionalized techniques and facilities, second hand markets and knowledge about bioplastics which, in the end, leads to a lack of sustainability.